Is DNA a Good Model Polymer? - Tree, Douglas R; Muralidhar, Abhiram; Doyle, Patrick S; Dorfman, Kevin D (Macromolecules, 2013)
The details surrounding the crossover from wormlike-specific to universal polymeric behavior has been the subject of debate and confusion even for the simple case of a dilute, unconfined wormlike chain. We have directly computed the polymer size, form factor, free energy, and Kirkwood diffusivity for unconfined wormlike chains as a function of molecular weight, focusing on persistence lengths and effective widths that represent single-stranded and double-stranded DNA in a high ionic strength buffer. To do so, we use a chain-growth Monte Carlo algorithm, the pruned-enriched Rosenbluth method (PERM), which allows us to estimate equilibrium and near-equilibrium dynamic properties of wormlike chains over an extremely large range of contour lengths. From our calculations, we find that very large DNA chains (≈1 000 000, base pairs depending on the choice of size metric) are required to reach flexible, swollen nondraining coils. Furthermore, our results indicate that the commonly used model polymer λ-DNA (48 500, base pairs) does not exhibit “ideal” scaling but exists in the middle of the transition to long-chain behavior. We subsequently conclude that typical DNA used in experiments are too short to serve as an accurate model of long-chain, universal polymer behavior.